Short Interval Infield Sarcoma Development following Resection of Glioblastoma and Adjuvant Radiotherapy and Temozolomide - Fahad E. Alotaibi; Kevin Petrecca (Case Reports in Medicine)
Background. The development of 2 unassociated brain cancers in the same patient is a rare occurrence. Secondary cancers are generally thought to develop as an oncogenic consequence of the radiation therapy delivered to treat the primary cancers, always requiring a significant time interval between radiation treatment and secondary cancer development. Case Description. We report the development of an undifferentiated myxoid sarcoma only 13 months following radiation therapy for a glioblastoma. Conclusion. This case represents the shortest time interval reported between radiation therapy and secondary brain cancer development.